Razširjenost in rastne značilnosti malega jesena (Fraxinus ornus L.) v Sloveniji - Piškur, Mitja (Gozdarski vestnik, 1999)
Growth characteristics of the flowering ash (Fraxinus ornus L.) hawe been analyzed on seven selected locations. On each of them seven or eight trees hawe been analyzed, 52 all together. Trunk analysis has been made first, followed by a ring analysis. Growth characteristics of the flowering ash were determined on seven stand locations according to social layers: growth in height and diameter growth according to age, and growth in height in dependence of diameter growth. Growth characteristics of the flowering ash differ according to social layers and sites. Phenomena of "pulling up" is significant for the flowering ash. It happens when the flowering ash in lower layers reacts and grows rapidly. When a stand canopy is made
Keywords: ekologija; habitat; mali jesen; morfologija; razširjenost; Slovenija; uporaba